High density cellulose nanofibril assembly leads to upgraded enzymatic and chemical catalysis of fermentable sugars, cellulose nanocrystals and cellulase production by precisely engineering cellulose synthase complexes. Issue 3 (20th January 2023) - Zhang, Ran; Hu, Zhen; Peng, Hao; Liu, Peng; Wang, Youmei; Li, Jingyang; Lu, Jun; Wang, Yanting; Xia, Tao; Peng, Liangcai
Abstract : High density cellulose nanofibril assembly for upgraded catalysis of sugars, cellulose nanocrystals and cellulases by precisely engineering cellulose synthases complexes. Abstract : Although cellulose represents the most abundant biomass resource on Earth, its natural recalcitrance hinders its application for low-cost biofuels and high-value bioproducts on a large scale. In this study, we generated less recalcitrant cellulose nanofibril substrates by site-specific mutations and knockouts of three OsCESA4, 7, 9 isoforms that are essential as cellulose synthase complexes for the cellulose biosynthesis of secondary cell walls in rice. As a comparison with the wild type form, three genetically-engineered CESAs isoforms independently generated cellulose nanofibrils with the average lengths reduced by 63%, which accounts for the high density of the amorphous cellulose chains as the initial breakpoints for the consistently enhanced biomass enzymatic hydrolysis into fermentable sugars. The genetically modified cellulose nanofibrils efficiently produce ideal nanocrystals with the most reduced dimension to-date in three knockout lines, which are applicable as optimal intermediates for highly valuable bioproducts. The improved cellulose nanofibrils are also effective in inducing the secretion of lignocellulose-degradation enzymes from fungi ( T. reesei ) with the two cellulase (exoglucanases, β-glucosidases) activities elevated by 100% and 138%, and the total protein level increased by 44%. Our data thus reveal a novel green strategy for achieving high-quality diverse bioproduction by integrating the precise genetic modification of lignocellulose substrates with efficient biomass process technology.